Company and CEO characteristics of climate change disclosure in Malaysia: A proposed empirical framework - Adlina, Farah Syafiqa; Junaidda, Ummi (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study examines how company-specific characteristics (profitability, size, leverage) and CEO traits (duality, tenure, education, and meeting attendance) influence Climate Change Disclosure (CCD) practices among Malaysian listed companies. Grounded in legitimacy theory, the research seeks to identify internal determinants of voluntary climate reporting in emerging markets. Methodology/approach: A quantitative content analysis is conducted on 114 Malaysian listed firms from four environmentally sensitive sectors during 2021–2022. Data are manually collected from annual and sustainability reports available on corporate websites and Bursa Malaysia. CCD is measured using a disclosure index based on TCFD recommendations. Descriptive statistics, Pearson correlation, and multiple regression analysis are employed to evaluate relationships between company and CEO characteristics and CCD. Results/findings: Findings reveal that company-level variables such as profitability, firm size, and leverage, alongside CEO attributes including duality, tenure, education, and meeting attendance, significantly affect CCD practices. Larger and more profitable firms, as well as CEOs with stronger educational backgrounds and greater governance engagement, are more likely to adopt higher disclosure levels. Conclusions: The study highlights the combined importance of structural and leadership factors in shaping CCD in Malaysia. It provides empirical insights to guide Malaysia’s transition toward compulsory climate reporting under IFRS S1 and S2. Limitations: The research focuses only on voluntary disclosures in four environmentally sensitive sectors, limiting generalization across industries. Contribution: This study contributes by integrating company and CEO characteristics into a single framework, offering implications for regulators, policymakers, and corporate governance reform in emerging economies.